Transnationalising Disability Studies: Rights, Justice and Impairment - Soldatic, Karen; Grech, Shaun (Disability Studies Quarterly, 2014)
In this paper we aim to explore the realm of impairment in terms of its politicization under transnational claims for justice. The realm of disability rights and justice has been a central theme in disability analytical inquiry and by disability movement actors engaged in struggles of disability affirmative politics. Within this frame, there has been an increasing amount of disability scholarship and activism at the transnational sphere. In fact, since the ratification of the UNCRPD (2006) greater transnational alliances have become a central feature to advancing disability affirmative claims for rights and justice. While welcomed, we argue that within the transnational realm, the focus on disability alone critically marginalizes those groups engaging in repertories of action within the logos of impairment as transnational claims for disability justice tend to naturalise impairment and negate the production of impairment under global structural processes of violence. To address this issue, we suggest that the growing scholarship on transnational theorizing and activism within disability needs to respond to these claims for justice and rights. To conclude we argue that transnational theorizing and praxis is in fact, a double move – an affirmative politics of disability rights and justice and a transformative politics of impairment. Keywords: impairment, justice, rights, disability politics, majority world, justice, North–South power relations, Southern epistemologies